NATO's secret armies : operation Gladio and terrorism in Western Europe - Ganser, Daniele (Frank Cass, 2005)
This fascinating new study shows how the CIA and the British secret service, in collaboration with the military alliance NATO and European military secret services, set up a network of clandestine anti-communist armies in Western Europe after World War II. These secret soldiers were trained on remote islands in the Mediterranean and in unorthodox warfare centres in England and in the United States by the Green Berets and SAS Special Forces. The network was armed with explosives, machine guns and high-tech communication equipment hidden in underground bunkers and secret arms caches in.
Keywords: North Atlantic Treaty Organization -- Armed Forces.; Gladio (Organization); Organisation du traité de l'Atlantique Nord -- Forces armées.; North Atlantic Treaty Organization; Paramilitary forces -- Europe, Western -- History -- 20th century.; Terrorism -- Europe, Western -- History -- 20th century.; Right-wing extremists -- Europe, Western -- History -- 20th century.; Forces paramilitaires -- Europe de l'Ouest -- Histoire -- 20e siècle.; Terrorisme -- Europe de l'Ouest -- Histoire -- 20e siècle.; Extrémistes de droite -- Europe de l'Ouest -- Histoire -- 20e siècle.; POLITICAL SCIENCE -- Political Freedom & Security -- Terrorism.; Armed Forces; Paramilitary forces; Right-wing extremists; Terrorism; Western Europe; 1900-1999; Electronic books.; History